Amine‐Responsive Disassembly of AuI–CuI Double Salts for Oxidative Carbonylation. (10th December 2019) - Cao, Yanwei; Yang, Jian‐Gong; Deng, Yi; Wang, Shengchun; Liu, Qi; Shen, Chaoren; Lu, Wei; Che, Chi‐Ming; Chen, Yong; He, Lin
Abstract: A sensitive amine‐responsive disassembly of self‐assembled Au I ‐Cu I double salts was observed and its utilization for the synergistic catalysis was enlightened. Investigation of the disassembly of [Au(NHC)2 ][CuI2 ] revealed the contribution of Cu‐assisted ligand exchange of N‐heterocyclic carbene (NHC) by amine in [Au(NHC)2 ] + and the capacity of [CuI2 ] − on the oxidative step. By integrating the implicative information coded in the responsive behavior and inherent catalytic functions of d 10 metal complexes, a catalyst for the oxidative carbonylation of amines was developed. The advantages of this method were clearly reflected on mild reaction conditions and the significantly expanded scope (51 examples); both primary and steric secondary amines can be employed as substrates. The cooperative reactivity from Au and Cu centers, as an indispensable prerequisite for the excellent catalytic performance, was validated in the synthesis of (un)symmetric ureas and carbamates. Abstract : Zerlegung für die Katalyse : Eine empfindliche amininduzierte Zerlegung selbstorganisierter Au I ‐Cu I ‐Doppelsalze wurde beobachtet. Angeregt durch diese Beobachtung und das Verständnis dieses dynamischen Prozesses wurde ein synergistisches Katalysesystem zur oxidativen Carbonylierung primärer und sekundärer Amine (51 Beispiele) zu Harnstoffen und Carbamaten entwickelt.